Disordered eating behaviours and correlates in yoga practitioners: a systematic review - Domingues, Rita B. (2019)
PurposeYoga has been increasingly used as a complementary therapy for eating disorders. However, it is still not clear whether yoga is effective in the prevention and treatment of eating disorders, as some studies suggest that yoga practitioners show elevated levels of disordered eating behaviours. The goal of this systematic review is, thus, to analyse the occurrence of disordered eating behaviours and correlates in yoga practitioners.MethodPRISMA guidelines for systematic reviews were used. Search was conducted in several databases and specific journals.ResultsTwelve articles, all cross-sectional, were identified, following PRISMA guidelines. Results across studies were inconsistent. Yoga practice was usually associated with healthier eating behaviours, lower disordered eating symptoms, and higher positive body image and body satisfaction, suggesting that yoga practitioners may be at a lower risk of developing eating disorders. However, other studies suggested that a high dosage of yoga practice may be associated with a higher prevalence of disordered eating behaviours.ConclusionsAs yoga is increasingly used as therapy for eating disorders, understanding the relationship between yoga dosage and disordered eating behaviours is critical to guide treatment recommendations and establish yoga as a valuable complementary therapy.Level of evidenceLevel I, systematic review.